Pelatihan Pemaafan Dalam Meningkatkan Kesejahteraan Subjektif, Kebahagiaan dan Hardiness Pada Mahasiswi yang Orantuanya Bercerai - Tasaufi, Muhammad Novvaliant Filsuf; Chandra, Novie kartika; Tyasari, Ratna Ridha; Sari, Azifa Kurnia (JIP : Jurnal Intervensi Psikologi, 2017)
Every child expects a harmonious family, but in reality, many conflicts occur so some family must end up in divorce. The impact of the divorce is the emergence of various negative emotions in children. The purpose of this study is to know the effectiveness of forgiveness therapy in improving subjective well-being, happiness, and hardiness of students whose parents are divorced. The method on this study were quasi experiments that used the training intervention of forgiveness. Subjects consisted of 12 female of undergraduate students consisting of 6 subjects of the experimental group and 6 subjects of the control group with the criteria of having parents who have divorced. The hypothesis proposed is that there is an influence of forgiveness in improving subjective wellbeing, happiness, and hardiness. Analysis was use non-parametric Mann U-Whitney. The results conclude that the hypothesis is rejected. The dynamics that occur will be reviewed in the discussion.Keywords: Forgiveness, Subjective Wellbeing, Happiness, Hardiness, Divorced Parents